Feasibility of Using 3D MR Elastography to Determine Pancreatic Stiffness in Healthy Volunteers - Shi, Yu (2014)
PURPOSE: To evaluate the feasibility of using 3D Magnetic Resonance Elastography (MRE) to determine the stiffness of the pancreas in healthy volunteers. MATERIALS AND METHODS: Twenty healthy volunteers underwent 1.5-T MRE exams using an accelerated echo planar imaging (EPI) pulse sequence with low-frequency vibrations (40 and 60 Hz). Stiffness was calculated with a 3D direct inversion algorithm. The mean shear stiffness in five pancreatic subregions (uncinate, head, neck, body and tail) and the corresponding liver stiffness were calculated. The intrasubject coefficient of variation (CV) was calculated as a measure of the reproducibility for each volunteer. RESULTS: The mean shear stiffness (average of values obtained in different pancreatic subregions) was (1.15±0.17) kPa at 40 Hz, and (2.09±0.33) kPa at 60 Hz. The corresponding liver stiffness was higher than the pancreas stiffness at 40 Hz [(1.60±0.21) kPa, mean pancreas-to-liver stiffness ratio: 0.72], but similar at 60Hz [(2.12±0.23) kPa, mean ratio: 0.95]. The mean intrasubject CV for each pancreatic subregion was lower at 40 Hz than 60 Hz (P<0.05 for all subregions, range: 11.9–15.7% at 40 Hz and 16.5–19.6% at 60 Hz). CONCLUSION: 3D pancreatic MRE can provide promising and reproducible stiffness measurements throughout the pancreas, with more consistent data acquired at 40 Hz.